Proposed scenario planning for Indonesia multinational pharmaceutical company in jaminan kesehatan nasional (jkn) era - Tri Nurmala, Devy; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Jaminan Kesehatan Nasional is one of the government's flagship programs to provide health services for all residents in Indonesia since 2014. The multinational pharmaceutical companies become one of the actors in supporting the successful of the program by providing innovative medicines. After the implementation, the government suffered losses in financing. The objective of this study is to propose a better strategy for pharmaceutical companies in Indonesia in support of the government's national health program. The discussion on this issue will be analyzed from an external point of view by using PESTEL (Political, Economic, Social, Technological, Environment, Legal) and from an Industry perspective using Porter's 5 Forces Analysis. In further analysis for internal use Resources based view, value chain analysis and SWOT analysis. The research method is qualitative by collecting data through interview and data observation. Scenario planning as a tool for drafting the strategy of multinational pharmaceutical companies within the next five years. In the formulation of a strategy, it is necessary to identify several factors which influence the issues thus lead to the two important uncertainties. The analysis then proceeded to create four scenarios followed by narratives. Furthermore, the implementation plan developed for each scenario.Â Keywords: scenario planning, multinational pharmaceutical company, innovative drugs, uncertainty, strategy